A cost effectiveness analysis of stepped care treatment for bulimia nervosa1. Issue 4 (28th January 2013) - Crow, Scott J.; Agras, W. Stewart; Halmi., Katherine A.; Fairburn, Christopher G.; Mitchell, James E.; Nyman, John A.
Abstract Background: The cost effectiveness of various treatment strategies for bulimia nervosa (BN) is unknown. Aims: To examine the cost effectiveness of stepped care treatment for BN. Method: Randomized trial conducted at four clinical centers with intensive measurement of direct medical costs and repeated measurement of subject quality of life and family/significant other time involvement. Two hundred ninety‐three women who met DSM‐IV criteria for BN received stepped care treatment or cognitive behavioral therapy. Cost effectiveness ratios were compared. Results: The cost per abstinent subject was 12, 146 for stepped care, and 20, 317 for cognitive behavioral therapy. Quality of life ratings improved significantly with treatment, and family/significant other time burden diminished substantially. Discussion: In this trial, stepped care for BN appeared cost effective in comparison to cognitive behavioral therapy. Treatment was associated with improved quality of life and diminished time costs of illness. © 2013 by Wiley Periodicals, Inc. (Int J Eat Disord 2013)